2017
DOI: 10.18869/acadpub.jsri.14.1.77
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Estimating Population Parameters Using Split Questionnaire Design

Abstract: Abstract. The effect of survey questionnaire length on precision of survey statistics has been discussed in several studies. It is generally concluded that the lengthy questionnaire leads to increase non-sampling errors, especially nonresponse rate. Split questionnaire method has been introduced as a solution to decrease the response burden and nonresponse rate, involves splitting the questionnaire into subquestionnaires and then administering these subquestionnaires to different subsets of the original sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For matrix survey sampling with overlapping subsets of questions, Merkouris (2015) proposed an efficient estimation method based on the principle of best linear unbiased estimation, generates composite optimal regression estimators of population totals. Kamgar and Navvabpour (2017) proposed a strategy to split long questionnaires and estimate the population parameters based on data collected from subquestionnaires. They examined the four methods of small-area estimation, Horvitz-Thompson estimation, regression method, and multiple imputation, and concluded that of these four methods if the appropriate auxiliary variables are used from the registers or previous census, the small-area estimation method gives us a more accurate estimate.…”
Section: Split Questionnaire Designmentioning
confidence: 99%
“…For matrix survey sampling with overlapping subsets of questions, Merkouris (2015) proposed an efficient estimation method based on the principle of best linear unbiased estimation, generates composite optimal regression estimators of population totals. Kamgar and Navvabpour (2017) proposed a strategy to split long questionnaires and estimate the population parameters based on data collected from subquestionnaires. They examined the four methods of small-area estimation, Horvitz-Thompson estimation, regression method, and multiple imputation, and concluded that of these four methods if the appropriate auxiliary variables are used from the registers or previous census, the small-area estimation method gives us a more accurate estimate.…”
Section: Split Questionnaire Designmentioning
confidence: 99%